Pengaruh Cetyltrimethylammonium Bromide pada Nilai Bandgap Semikonduktor TiO₂-ZnO - Olga Tiara Rizki; Hary Sanjaya (Lembaga Yasin AlSys, 2025)
This study aims to investigate the effect of adding the surfactant Cetyltrimethylammonium Bromide (CTAB) on the bandgap energy of the TiO₂-ZnO semiconductor material. The material was synthesized using the sol-gel method and characterized by UV-Vis diffuse reflectance spectroscopy (UV-Vis DRS). Variations in CTAB concentration (0.015–0.035 grams) were introduced to evaluate changes in the material’s optical properties. The results show that CTAB addition up to 0.025 grams reduced the bandgap energy from 3.225 eV to 3.004 eV. This decrease is attributed to the formation of structural defects such as oxygen vacancies and reduced particle size, which introduce additional energy states within the bandgap. However, further addition of CTAB beyond 0.025 grams led to an increase in bandgap energy, likely due to particle agglomeration and structural disruptions. These findings indicate that CTAB not only acts as a surfactant but also plays a role in tuning the structure and optical properties of TiO₂-ZnO. Therefore, optimizing CTAB concentration is crucial for enhancing the material's performance in photocatalytic and solar cell applications.